Electronic commerce adoption in SME: The trend of prior studies - Mohamad, Rosli; Ismail, Noor Azizi (ARRAY Development, 2009)
Emergence of Internet, particularly Electronic Commerce (EC) application brings new landscape in conducting business. Apart of better efficiency, EC enables firm to diversify business strategy, to introduce newly accepted business model and to embrace globalization. Despite profound usage among large firms, EC is now getting attention of small medium-sized enterprises (SMEs). This is obviously raises concern as small firms have long been recognized for limited resources and capabilities than larger firms. Consequently, the issue of EC in SMEs attracts considerable research works in this area. This conceptual paper reports on the extensive review of prior studies pertaining to the EC usage among small firms. This paper, however, limits the review to several major aspects i.e. research themes, underpinning theories, research approaches, and the context/country of the study. The last section then outlines important findings of the previous studies and future research direction.